Enhancing Number Recognition Through Concrete Media-Based Project Learning: An Action Research Study with Children at Risk of Learning Difficulties - Sumartin, Santy; Suparno, Suparno (Papanda Publisher, 2025)
Number recognition represents a fundamental cognitive milestone in early childhood development, yet children with learning difficulties often struggle with abstract mathematical concepts. This study investigated the effectiveness of concrete media-based project learning in enhancing number recognition abilities among kindergarten children at risk of learning difficulties. An action research design following the Kemmis and McTaggart model was implemented over three iterative cycles from January to May 2025. The participant was a 5-6 year-old child identified with learning difficulties at TK Negeri Pembina, East Kalimantan, Indonesia. The intervention employed Project-Based Learning methodology through a